Keberatan Pihak Ketiga Yang Beritikad Baik Terhadap Perampasan Aset Dalam Tindak Pidana Korupsi - Evander (Jurist-Diction, 2024)
Abstract Evidence is an item of crime and one of the important pieces of evidence in uncovering a crime. Evidence is not always owned by the Defendant but is under the control of a third party with good intentions. This action violated the provisions of Article 28H paragraph (4) of the 1945 Constitution where third party property rights were taken by force. To respond to these problems, Article 19 paragraph (2) of the PTPK Law has protected third parties who have good intentions through "Keberatan” but there are limitations in submitting them so that they violate article 573 BW. The breach was resolved with the advent of PERMA 2/2022. PERMA 2/2022 stipulates that "Keberatan” can be filed based on a first level decision, appeal or cassation. The addition of norms in PERMA 2/2022 raises a problem where Article 19 paragraph (2) of the PTPK Law and PERMA 2/2022 are not aligned and there are legal issues, namely whether there is a conflict of norms. Keywords: evidence, "PERMA 2/2022”, Article 19 paragraph (2) of the "PTPK” Law, "Keberatan”, third party with good intentions.   Abstrak Barang bukti merupakan barang kejahatan dan salah satu alat bukti penting dalam mengungkap kejahatan. Barang bukti tidak selalu dimiliki oleh Terdakwa tetapi berada dibawah kekuasaan pihak ketiga yang beritikad baik. Tindakan tersebut melanggar ketentuan Pasal 28H ayat (4) UUD 1945 dimana hak milik pihak ketiga diambil secara paksa. Untuk menanggapi permasalahan tersebut, Pasal 19 ayat (2) UU PTPK telah melindungi pihak ketiga yang beritikad baik lewat upaya Keberatan tetapi terdapat batasan dalam mengajukannya sehingga melanggar pasal 573 BW. Pelanggaran tersebut diselesaikan dengan munculnya PERMA 2/2022. PERMA 2/2022 mengatur bahwa Keberatan dapat diajukan berdasarkan putusan tingkat pertama, banding atau kasasi. Penambahan norma dalam PERMA 2/2022 tersebut menimbulkan permasalahan dimana pasal 19 ayat (2) UU PTPK dengan PERMA 2/2022 tidak selaras dan terdapat isu hukum, yakni apakah terjadi konflik norma.  Kata Kunci: barang bukti, PERMA 2/2022, pasal 19 ayat (2) UU PTPK, Keberatan, pihak ketiga yang beritikad baik